Association of spontaneous abortion with all cause and cause specific premature mortality: prospective cohort study. (24th March 2021) - Wang, Yi-Xin; Mínguez-Alarcón, Lidia; Gaskins, Audrey J; Missmer, Stacey A; Rich-Edwards, Janet W; Manson, JoAnn E; Pan, An; Chavarro, Jorge E
Abstract: Objective: To investigate the association of spontaneous abortion with the risk of all cause and cause specific premature mortality (death before the age of 70). Design: Prospective cohort study. Setting: The Nurses' Health Study II (1993-2017), United States. Participants: 101 681 ever gravid female nurses participating in the Nurses' Health Study II. Main outcomes measures: Lifetime occurrence of spontaneous abortion in pregnancies lasting less than 6 months, determined by biennial questionnaires. Hazard ratios and 95% confidence intervals for all cause and cause specific premature death according to the occurrence of spontaneous abortion, estimated with time dependent Cox proportional hazards models. Results: During 24 years of follow-up, 2936 premature deaths were recorded, including 1346 deaths from cancer and 269 from cardiovascular disease. Crude all cause mortality rates were comparable for women with and without a history of spontaneous abortion (1.24 per 1000 person years in both groups) but were higher for women experiencing three or more spontaneous abortions (1.47 per 1000 person years) and for women reporting their first spontaneous abortion before the age of 24 (1.69 per 1000 person years). The corresponding age adjusted hazard ratios for all cause premature death during follow-up were 1.02 (95% confidence interval 0.94 to 1.11), 1.39 (1.03 to 1.86), and 1.27 (1.11 to 1.46), respectively. After adjusting for confounding factors and updated dietary and lifestyle factors, the occurrence of spontaneous abortion was associated with a hazard ratio of 1.19 (95% confidence interval 1.08 to 1.30) for premature mortality during follow-up. The association was stronger for recurrent spontaneous abortions (hazard ratio 1.59, 95% confidence interval 1.17 to 2.15 for three or more spontaneous abortions; 1.23, 1.00 to 1.50 for two; and 1.16, 1.05 to 1.28 for one compared with none), and for spontaneous abortions occurring early in a woman's reproductive life (1.32, 1.14 to 1.53 for age ≤23; 1.16, 1.01 to 1.33 for ages 24-29; and 1.12, 0.98 to 1.28 for age ≥30 compared with none). When cause specific mortality was evaluated, the association of spontaneous abortion with premature death was strongest for deaths from cardiovascular disease (1.48, 1.09 to 1.99). Spontaneous abortion was not related to premature death from cancer (1.08, 0.94 to 1.24). Conclusions: Spontaneous abortion was associated with an increased risk of premature mortality, particularly death from cardiovascular disease.